Fostering Generative Learning from Video Lessons: Benefits of Instructor-Generated Drawings and Learner-Generated Explanations - Fiorella, Logan; Stull, Andrew T; Kuhlmann, Shelbi; Mayer, Richard E (Journal of educational psychology, 2020)
This study explored ways to foster generative learning during a narrated video lesson about the human kidney. In a 2 × 3 between-subjects design, 196 college students were randomly assigned to a video format condition and a learning strategy condition. Students listened to oral explanations from the instructor as they viewed either a series of static diagrams (static visuals) or the same diagrams dynamically drawn on the screen without the instructor visible (instructor-generated visuals). After each part of the lesson, students either wrote verbal explanations (explain) or created drawings (draw), or they rewatched that part of the lesson (rewatch). All students then completed retention and transfer tests on the material. Results indicated a significant main effect of learning strategy for retention and transfer: the explain group significantly outperformed the draw group (retention: d = 0.60; transfer: d = 0.67) and the rewatch group (retention: d = 0.58; transfer d = 0.87). There was also a significant video format by learning strategy interaction for transfer: explaining was most effective for students who observed instructor-generated visuals (ds > 1.0) rather than static visuals (ds < 0.5). These findings suggest that when learning from narrated video lessons with complex diagrams, students benefit most from viewing dynamically generated drawings and then verbally explaining what they learned. In contrast, creating drawings may not be appropriate for learning from diagram-heavy lessons. Overall, this study demonstrates the importance of aligning instructional methods with appropriate learning strategies.